Mapping intervention components from a randomized controlled trial to scale-up of an early life nutrition and movement intervention: The INFANT program - Marshall, Sarah; Johnson, Brittany J.; Hesketh, Kylie D.; Campbell, Karen J.; Fraser, Kylie; Love, Penelope; Denney-Wilson, Elizabeth; Salmon, Jo; McCallum, Zoe; Laws, Rachel (Frontiers in Public Health, 2023)
Introduction Early life parent-focused interventions can effectively improve infant and child nutrition and movement (physical activity and sedentary behavior) as well as parents' health behaviors. Scale-up of such interventions to real-world settings is essential for population-wide benefits. When progressing to scale-up, intervention components may be modified to reflect contextual factors and promote feasibility of scale-up. The INFANT program, an efficacious early life nutrition and movement behavioral intervention began as a randomized controlled trial (RCT), was modified after a small-scale translation, and is currently being scaled-up in Victoria, Australia. This study mapped and compared discrete intervention components of both the original RCT and the scaled-up version of INFANT to examine modifications for scaling up. Methods Discrete intervention components, specifically the target behaviors (child-related and parent-related behaviors), delivery features and behavior change techniques (BCTs) from the RCT and the scaled-up program were coded and mapped using established frameworks and taxonomies. Publications and unpublished materials (e.g., facilitator notes, handouts, videos, app) were coded. Coding was performed independently in duplicate, with final coding validated in a meeting with interventionists. Interventionists reported the rationale for modifications made. Results The INFANT RCT and scaled-up version targeted the same obesity prevention-related nutrition and movement behaviors. Key modified delivery features at scale-up included reduced number of sessions, a broader range of professionals facilitating groups, the addition of a mobile app for parents replacing hard-copy materials and tangible tools (e.g., pedometers), and broadening of content (e.g., early feeding, updated 24-h movement guidelines). BCTs used across the RCT and scale-up sessions were unchanged. However, the BCTs identified in the between-session support materials were almost double for the scale-up compared with the RCT, primarily due to the reduced number of sessions and the app's capacity to include more content. Conclusions INFANT is one of few early life nutrition and movement behavioral interventions being delivered at scale. With INFANT as an example, this study provides critical understanding about what and why intervention components were altered as the RCT was scaled-up. Unpacking these intervention modifications provides important insights for scale-up feasibility, outcome effects, and how to optimize implementation strategies for population-level benefits.